L’anticommunisme de la droite gouvernementale dans la vie politique française de 1968 à 1984 - Laurent Jalabert (Les Cahiers de Framespa)
The period from the events of May 1968 to the election of François Mitterrand shows that anti-communism in France is experiencing an undeniable revival in the political circles of the parliamentary right. Animated by old fantasies about the "fear of the red" in the most conservative circles in the 1960s, it found in part of the Gaullist government of the late 1960s and around the events of 1968, a fierce revival, an argument that carried weight in the political struggle that was confirmed by the legislative elections of June 1968. The debate undoubtedly intensified in the 1970s, around the socialist-communist alliance born of the Common Government Programme. The right, very fearful of a possible changeover, did not hesitate to multiply the amalgams. François Mitterrand and the SP were said to be prisoners of the FCP. All the arguments were used, in particular the programmed deprivation of freedoms, the economic misery in prospect, totalitarianism as a project... a caricature which was based for the most part on negative representations of the communist world. The movement was maintained and then slowly eroded in the early 1980s.